Perceived Stress of Quarantine and Isolation During COVID-19 Pandemic: A Global Survey - Huy, Nguyen T.; Nguyen Tran, Minh Duc; Mohammed Alhady, Shamael T.; Luu, Mai N.; Hassan, Amr K.; Giang, Tran V.; Truong, Le V.; Ravikulan, Rohanti; Raut, Akshay P.; Dayyab, Farouq M.; Durme, Shyam P.; Trang, Vu T.; et al. (Frontiers in Psychiatry, 2021)
Aims: Understanding of the perceived stress and coping strategies adopted by people is important for contemplating the consequences of a pandemic on mental health of people globally. In this study, we intended to assess the perceived stress status under quarantine/isolation globally during the COVID-19 pandemic. Methods: This is a multicentre, multinational cross-sectional study that recruited isolated/quarantined individuals suspected or confirmed to have COVID-19 to assess the psychological impact of the quarantine/isolation experience by answering a survey distributed online. Results: The study was conducted across 63 participating countries, gaining 1,871 valid responses. There was a higher proportion of female participants in the Moderate to High Perceived Stress Scores (MH-PSS) group compared to the Low Perceived Stress Score group (66.0 vs. 52.0%) and a higher proportion of individuals whose marital status was single had MH-PSS (57.1%). Also, individual's religion (Christian, Hindu, and Muslim), no formal education level, being exposed to a confirmed or suspected COVID-19 patient, being forced to be quarantined/isolated, uncomfortable feeling during quarantine period may significantly increase the risk of MH-PSS (p < 0.05). Conclusions: Many factors can predict stress in COVID-19 pandemic including female sex, being single, religion, no formal education, involuntary quarantine, location and reason of quarantine/isolation, and place of exposure.